The Lymphatic System in Obesity, Insulin Resistance, and Cardiovascular Diseases - Jiang, Xinguo; Tian, Wen; Nicolls, Mark R.; Rockson, Stanley G. (Frontiers in Physiology, 2019)
Obesity, insulin resistance, dyslipidemia, and hypertension are fundamental clinical manifestations of the metabolic syndrome. Studies over the last few decades have implicated chronic inflammation and microvascular remodeling in the development of obesity and insulin resistance. Newer observations, however, suggest that dysregulation of the lymphatic system underlies the development of the metabolic syndrome. This review summarizes recent advances in the field, discussing how lymphatic abnormality promotes obesity and insulin resistance, and, conversely, how the metabolic syndrome impairs lymphatic function. We also discuss lymphatic biology in metabolically dysregulated diseases, including type 2 diabetes, atherosclerosis, and myocardial infarction.